2013
DOI: 10.1155/2013/916408
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Agronomic Practices with Herbicides for Sustainable Weed Management in Aerobic Rice

Abstract: Till now, herbicide seems to be a cost effective tool from an agronomic view point to control weeds. But long term efficacy and sustainability issues are the driving forces behind the reconsideration of herbicide dependent weed management strategy in rice. This demands reappearance of physical and cultural management options combined with judicious herbicide application in a more comprehensive and integrated way. Keeping those in mind, some agronomic tools along with different manual weeding and herbicides com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Due the higher weed suppressive ability, hybrid rice yielded 15-25% more over inbred cultivars (Walker et al, 2008;Dass et al, 2017). Therefore, through selection of weed competitive cultivars, the weed emergence and its subsequent growth can be suppressed and at the same time reduce the cost of weed management Gibson et al, 2002;2003;Zhao et al, 2006;Rao et al, 2007;Mahajan and Chauhan, 2011;Anwar et al, 2013;Dass et al, 2017). Whereas, Lemerle et al (1996) and reported a higher weed control in combination system of herbicides with crop species or genotypes of superior competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Due the higher weed suppressive ability, hybrid rice yielded 15-25% more over inbred cultivars (Walker et al, 2008;Dass et al, 2017). Therefore, through selection of weed competitive cultivars, the weed emergence and its subsequent growth can be suppressed and at the same time reduce the cost of weed management Gibson et al, 2002;2003;Zhao et al, 2006;Rao et al, 2007;Mahajan and Chauhan, 2011;Anwar et al, 2013;Dass et al, 2017). Whereas, Lemerle et al (1996) and reported a higher weed control in combination system of herbicides with crop species or genotypes of superior competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the application of pretilachlor þ safener fb propanil/thiobencarb reduced weed density by 60% compared with the weedy treatment. This reduction was further increased to 75% with the application of pretilachlor þ safener fb propanil/thiobencarb fb bentazon/MCPA (Anwar et al, 2013).…”
Section: Tablementioning
confidence: 98%
“…Depending on the season, location, and management practices used, DSR systems can save total labour requirements by 11e66% and irrigation water need by 35e57% (Bhushan et al, 2007;Jat et al, 2009) compared with puddled transplanted rice. However, one factor that hampers the sustainability and profitability of DSR systems is the prevalence and infestation of weeds, thus, efforts are being made to develop effective and sustainable weed management strategies for these systems (Singh et al, 2006;Anwar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentiality of using weed competitive variety in integrated weed management has been documented in many crops including rice [44]- [49]. The deployment of weed competitive variety is not only ecofriendly [50] [51] but also a very cost effective [52] [53]. No work has so far been done to assess the ability of the huge pool of Bangladeshi rice germplasms to wrestle weeds under aerobic soil conditions.…”
mentioning
confidence: 99%